Underage Adolescents' Reactions to Adverts for Beer and Spirit Brands and Associations with Higher Risk Drinking and Susceptibility to Drink: A Cross-Sectional Study in the UK. (23rd April 2021) - Boniface, S; Critchlow, N; Severi, K; MacKintosh, A M; Hooper, L; Thomas, C; Vohra, J
Abstract: Aims: In the UK, adolescents under the minimum legal purchasing age (<18 years) are aware of a variety of alcohol marketing activities. It is therefore important to examine how such marketing appeals and how it might shape consumption. This study assessed the relationships between positive reactions to alcohol adverts and susceptibility to drink among never drinkers and higher-risk drinking among current drinkers. Methods: Online cross-sectional survey of 11–17 year olds ( n = 2582) in the UK. Adolescents were shown three video alcohol adverts (Fosters Radler/Haig Club Clubman/Smirnoff). Reactions to each were measured by eight scale-items (e.g. 1 = makes [Brand] seem unappealing to 5 = makes [Brand] seem appealing), which were combined into a composite score (coded: positive versus other). Logistic regressions assessed associations between overall positive advert reactions and drinking behaviours. Results: Half of adolescents had overall positive reactions to the Smirnoff (52%) and Fosters (53%) adverts, and a third (34%) had a positive reaction to the Haig Club advert. Across all three adverts, positive reactions were associated with 1.5 times increased odds of being susceptible to drink among never drinkers. Among current drinkers, positive reactions to the Foster's Radler and Haig Club adverts were associated with around 1.4 times increased odds of being a higher-risk drinker. Conclusions: These alcohol advertisements commonly appealed to underage adolescents, and these reactions were associated with susceptibility among never drinkers and higher-risk consumption among current drinkers. Regulatory consideration should be given to what messages are permitted in alcohol advertising, including international alternatives (e.g. only factual information). Abstract : Short Summary: This cross-sectional study builds on earlier work which established underage adolescents are aware of various alcohol marketing activities. Between a third and half of underage UK adolescents reacted positively to the alcohol adverts studied. Positive reactions were associated with increased susceptibility among never drinkers and higher-risk drinking among current drinkers.